Beyond Dietary Diversity: Household and Dietary Determinants of Wasting in Indonesian Children - Riska Mayang Saputri Ginting; Sepsina Reski (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Indonesia is experiencing a triple burden of malnutrition—undernutrition, overnutrition, and micronutrient deficiencies. Wasting reflects acute nutritional imbalance caused by inadequate dietary intake and infection. Evidence linking dietary diversity, household food security, and wasting remains limited, particularly in the Puskesmas Mangkupalas area. Objective : To assess the associations between dietary diversity, household food security, and other related factors with wasting among children aged 6–23 months in Puskesmas Mangkupalas. Research Methods : A cross-sectional study was conducted among 137 children aged 6–23 months from Puskesmas Mangkupalas, selected through purposive sampling. Data collected included sociodemographic characteristics, dietary diversity, 24-hour dietary recall, anthropometric measurements, macronutrient intake, and household food security. Spearman correlation tests were used to examine associations between variables. Results : The triple burden was evident, with 40.1% of children wasted and 11.7% overweight or obese. Nearly half (48.9%) consumed non-diverse diets. Dietary diversity (p = 0.100) and household food security (p = 0.379) were not significantly associated with wasting. Significant correlates included the presence of smokers in the household, recent child illness, market proximity, household income, and macronutrient intake—energy (p = 0.001, r = 0.354), fat (p = 0.048), and carbohydrates (p < 0.001). Conclusion/Lesson Learned : The coexistence of wasting and overweight reflects the ongoing nutrition transition. Addressing this issue requires multi-sectoral actions prioritizing modifiable household and dietary factors—such as smoking exposure, market access, and energy adequacy— beyond dietary diversity and food security measures to effectively reduce acute malnutrition.